A New Illustrated History of the Book - Navickienė, Aušra (Knygotyra, 2021)
THE OXFORD ILLUSTRATED HISTORY OF THE BOOK. EDITOR JAMES RAVEN. OXFORD UNIVERSITY PRESS, 2020. 480 P. ISBN 9780198702986. EBOOK ISBN 9780191007507.